Assurance and Advisory Intern - Bhatia, Jahanvi (ATLAS SkillTech University, 2024)
My internship with Sudit K Parekh & Co LLP was in the Attest & Advisory (Audit) department. The role included handling audit work of different companies. Throughout my internship, I undertook diverse responsibilities that significantly contributed to the growth and success of the platform.
Project Report on Assurance and Advisory Intern’ (2022-24) Under the Guidance of Prof. Chetana Asbe
Keywords: Audit